Pengaruh Endorsement Selebriti dan Persepsi Kualitas Terhadap Keputusan Pembelian Produk Glad2glow pada Toko Novita Kosmetik Kabupaten Luwu - Askar, Pajrin; Jusri; Irwan, Andi Muhammad; Hasnidar (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to analyze the influence of celebrity endorsements and perceived quality on purchasing decisions for Glad2Glow products at Novita Cosmetics. Celebrity endorsements are a marketing strategy widely used by companies to influence consumers in making purchasing decisions. This study employed a quantitative method. The population was comprised of customers who purchased Glad2Glow products at Novita Cosmetics. A sample size of 50 respondents was selected. The sampling method used was saturated sampling. Data collection methods included observation, questionnaires, documentation, and literature review. Validity and reliability tests were used to test the instruments. Multiple linear regression, t-tests, and f-tests were used to test the hypotheses. The partial t-test results from the table show a significance level of 0.045 (X1) and 0.000 (X2) <0.05, and calculated t-values ​​of 2.060 (X1) and 4.520 (X2), which are greater than the t-value of 2.011. The results of this study indicate that celebrity endorsement and perceived quality have a positive influence on purchasing decisions.